Most microRNAs in the single-cell alga Chlamydomonas reinhardtii are produced by Dicer-like 3-mediated cleavage of introns and untranslated regions of coding RNAs - Valli, Adrian A.; Santos, Bruno A.C.M.; Hnatova, Silvia; Bassett, Andrew R.; Molnar, Attila; Chung, Betty Y.; Baulcombe, David C. (Genome Research, 2016)
We describe here a forward genetic screen to investigate the biogenesis, mode of action, and biological function of miRNA-mediated RNA silencing in the model algal species, Chlamydomonas reinhardtii. Among the mutants from this screen, there were three at Dicer-like 3 that failed to produce both miRNAs and siRNAs and others affecting diverse post-biogenesis stages of miRNA-mediated silencing. The DCL3-dependent siRNAs fell into several classes including transposon- and repeat-derived siRNAs as in higher plants. The DCL3-dependent miRNAs differ from those of higher plants, however, in that many of them are derived from mRNAs or from the introns of pre-mRNAs. Transcriptome analysis of the wild-type and dcl3 mutant strains revealed a further difference from higher plants in that the sRNAs are rarely negative switches of mRNA accumulation. The few transcripts that were more abundant in dcl3 mutant strains than in wild-type cells were not due to sRNA-targeted RNA degradation but to direct DCL3 cleavage of miRNA and siRNA precursor structures embedded in the untranslated (and translated) regions of the mRNAs. Our analysis reveals that the miRNA-mediated RNA silencing in C. reinhardtii differs from that of higher plants and informs about the evolution and function of this pathway in eukaryotes.
10.1101/gr.199703.115